Theorising from global south literature for praxis: a transnational approach to chameleon feminism. (December 2022) - Deb, Basuli
This article challenges the historical directionality of women's knowledge and experience from the global north to the global south. It situates Moroccan feminist literature by Leila Abouzeid and Malika Oufkir within a transnational comparative approach to argue that reversing such flows – northward instead of southward – enables defamiliarising feminist theory as we know it to refamiliarise it for feminist praxis. Drawing on Obioma Nnaemeka's African feminist philosophy, the article engages in a literary analysis to articulate a theory of 'chameleon feminism' for illuminating how global south women's stories connect rooms, arenas and fields for a praxis of resilience against authoritarianism.